THROMBOCYTOPENIA PREVALENCE AND SEVERITY ASSESSMENT IN PLASMODIUM VIVAX MALARIA PATIENTS - Muhammad Numan Saleem; Muhammad Younas; Roman Wazir; Iqra; Khalid Nawaz; Waqas Fazal; Rizwanullah; Ashish Sharma; Waqar Khan; Suleman Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Thrombocytopenia, characterized by reduced platelet counts, is a known consequence of various malaria infections. Nevertheless, its occurrence and clinical significance in Plasmodium vivax malaria have received limited attention. While thrombocytopenia and anemia are frequently observed abnormalities, this study aims to assess thrombocytopenia in Plasmodium vivax malaria patients, providing insights into the risk of severe thrombocytopenia. Methodology: This descriptive cross-sectional study was carried out at Hayatabad Medical Complex in Peshawar, Pakistan. A total of 297 cases were included in the study using a consecutive non-probability sampling method. Patients of both genders between ages 18 to 60 years, with smear-positive VIVAX malaria who had a fever exceeding 100 degrees Fahrenheit for at least one day were included. Confounding factors were managed through strict adherence to exclusion criteria. Result: Thrombocytopenia was highly prevalent among Vivax Malaria patients, affecting 82.83% of cases, with 17.17% remaining unaffected. Most patients experienced mild or moderate thrombocytopenia, while severe cases were rare (1.35%). Analysis by age revealed a slight increase in older patients. Prevalence of thrombocytopenia was 80.9% for ≤30 years, 81.4% for 31-40 years, 84.5% for 41-50 years, and 89.5% for >50 years. Gender-based analysis showed a slightly higher prevalence in females (83.2%) versus males (82.6%), though not statistically significant. Conclusion: These findings highlight the importance of monitoring platelet counts and comprehending the clinical significance of thrombocytopenia in vivax malaria management. Further research is needed to gain a comprehensive understanding of the underlying mechanisms and clinical implications of thrombocytopenia in vivax malaria.